2020
DOI: 10.1016/j.jhazmat.2020.122411
|View full text |Cite
|
Sign up to set email alerts
|

Are males and females of Populus cathayana differentially sensitive to Cd stress?

Abstract: This study clarifies the mechanisms of Cd uptake, translocation and detoxification in Populus cathayana Rehder females and males, and reveals a novel strategy for dioecious plants to cope with Cd contamination. Females exhibited a high degree of Cd uptake and root-to-shoot translocation, while males showed extensive Cd accumulation in roots, elevated antioxidative capacity, and effective cellular and bark Cd sequestration. Our study also found that Cd is largely located in epidermal and cortical tissues of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 62 publications
4
14
0
Order By: Relevance
“…In our results, both male and female P. cathayana mainly enriched U in their roots, which is consistent with previous studies that showed that roots were the primary part of plants such as Amaranthus [33], sunflowers [34], and poplar trees [20,35] to accumulate heavy metals, including U. In further comparison with female trees, the male P. cathayana exhibited significantly higher U accumulation ability in roots without U detected in U can inhibit the growth of poplar [29], including plant height and biomass.…”
Section: Sex Differences In Growth U Enrichment and Distributionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our results, both male and female P. cathayana mainly enriched U in their roots, which is consistent with previous studies that showed that roots were the primary part of plants such as Amaranthus [33], sunflowers [34], and poplar trees [20,35] to accumulate heavy metals, including U. In further comparison with female trees, the male P. cathayana exhibited significantly higher U accumulation ability in roots without U detected in U can inhibit the growth of poplar [29], including plant height and biomass.…”
Section: Sex Differences In Growth U Enrichment and Distributionsupporting
confidence: 93%
“…If resources are limited, reproduction directly competes with the other two processes (vegetative growth and stress resistance) [17][18][19]. Male trees experience non-biological stresses, such as ultraviolet radiation, temperature, humidity, and heavy metals, and are more resistant to these stressors than females [20,21]. With limited resources, female trees often invest more energy in reproduction, whereas male trees devote more resources to vegetative growth and stress resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Poplars are dioecious species, in which females and males have significant differences in biomass partitioning, photosynthesis, carbon-nutrient balance and leaf anatomical traits when exposed to abiotic stresses, including salt stress , Chen et al 2016, Liu et al 2020a, Liu et al 2021, which is further affected by N forms (Chen et al 2011, Liu et al 2020b. Poplars preferentially take up NO3 − when both NH4 + and NO3 − are given at the same concentration, and growth may be accelerated despite high energy requirements (Bi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in-vivo and in-vitro experiments have shown that Cd is a mutagen that inhibits DNA repair 8 and reproductive function; experiments in rat testes showed inhibition by PI3K with the mammalian target of rapamycin (mTOR) signaling pathway, which is associated with autophagy and apoptosis 9 . Notably, females were more vulnerable to Cd exposure than males 10 , which would increase the risk of breast cancer (Dietary intake and urinary level of cadmium and breast cancer risk: A meta-analysis).…”
Section: Introductionmentioning
confidence: 99%